Study guides

☆☆

Q: 2x plus 3 equals 4x-11

Write your answer...

Submit

Related questions

khjgfsddfghjfghjk

(2x + 3)(2x + 3)

2x+3=9 2x=9-3 2x=6 2x/2=6/2 X=3

2x = x+3 2x-x = 3 x = 3

(0, -3)

4x + 3 = -3 + 2x + 14 2x + 3 = -3 +14 2x + 3 = 11 2x = 8 x=4

(-1, 3)

if 2x+3=9 then 2x=6 so x=3

2x + 3 = -92x = -12x = -6

2x=x+3=x=3

2x = 4x + 3 -2x = 3 x = -3 / 2

the converse of this conditional is true

x=3

3

x=3.

2x + 3 = 9 2x = 6 x = 3

2x+3 = 9x 3 = 9x-2x = 7x 7x = 3 x = 3/7

2x+3 = 7 2x = 7-3 2x = 4 x = 2

It is: y = 2x-3

Do you need this equation factored or? 2x+3=x+4?

x + 3 = 2x 3 = x x cannot be 2

2x+3 = -11 2x = -11-3 2x = -14 x = -7

X = -3

2x + 3y = 1 y = 1/3 - 2x/3

4